The Role of Educational Technology Based on The Use of Adobe Premiere Pro in Teaching Arabic Remotely Via Videos in The Covid-19 Pandemic: دور تكنولوجيا التعليم على أساس استخدام برنامج أدوب بريمير برو في تعليم اللغة العربية عن بعد عبر الفيديوهات في ضوء جائحة كوفيد 19 - Triadi Wicaksono (Journal of Arabic Language Teaching, 2021)
The role of learning media in teaching and learning is an integral part of the world of Education. Learning Media is everything that can be used to convey messages from teachers to students, to stimulate the thinking power, feelings, and interest of students to learn. In addition, the media can play a role in overcoming the boredom of studying in the classroom. Therefore, teachers must motivate students through various media that are not limited only to the school. COVID-19 is a disease caused by a new coronavirus called SARS-CoV-2. The World Health Organization first became aware of the new virus on December 31, 2019, after reports of a cluster of "viral pneumonia" cases in Wuhan, people's Republic of China. The outbreak of this disease disrupted all face-to-face learning classes around the world. All learning processes are then converted into virtual space through various electronic means, including creating learning materials through videos. To produce high-quality videos, teachers need special computer programs. Adobe Premiere Pro is one of the leading computer programs in creating videos, commercials, and movies, in terms of editing, effects, modifying video clips, and addiessentialmportant unique additions. This research method is a qualitative research based on descriptive studies on the Adobe Premiere Pro program and its characteristics in teaching Arabic. The result of the study is that the program has both advantages and disadvantages and can significantly benefit teaching Arabic, especially in circumstances that do not allow direct reflection in the classroom and teachers are forced to innovate in the distance education system. يعتبر دور وسائط التعلم في عملية التعلم والتعليم جزءًا لا يتجزأ من عالم التربية والتعليم. وسائل الإعلام التعليمية هي كل ما يمكن استخدامه لتوجيه رسالة المرسل إلى المتلقي، بحيث يمكن أن تحفز أفكار ومشاعر واهتمامات الطلاب على التعلم. بالإضافة إلى ذلك، يمكن لوسائل الإعلام أن تلعب دورًا في التغلب على الملل في التعلم في الفصول الدراسية. لذلك، يتعين على المعلمين توفير الحافز للطلاب من خلال استخدام الوسائط التي لا تكون في الفصل فقط. كوفيد 19 هو المرض الناجم عن فيروس كورونا جديد يسمى SARS-CoV-2. علمت منظمة الصحة العالمية بهذا الفيروس الجديد لأول مرة في 31 ديسمبر 2019، بعد تقرير عن مجموعة من حالات “الالتهاب الرئوي الفيروسي” في ووهان، جمهورية الصين الشعبية. فتفشي هذا المرض يؤدي إلى تعطيل جميع المحاضرات الصفية داخل القاعات الدراسية على مستوى العالم. فتنتقل العملية التعليمية إلى القاعات الافتراضية عبر وسائل إلكترونية شتى منها إنشاء المحاضرات عبر الفيديوهات. ولإخراج الفيديوهات ذات جودة عالية بحاجة إلى برامج حاسوب متخصصة. ومن أبرز برامج الحاسوب المتخصصة في عمل مقاطع الفيديوهات والإعلانات والأفلام، وهذا عن طريق التحرير والتأثير والتعديل على مقاطع الفيديو وأيضاً إضافة بعض الإضافات المهمة المختلفة برنامج أدوب بريمير برو. ومنهج هذا البحث هو بحث كيفي يقوم على دراسات وصفية للبرنامج وخصائصه في تعليم اللغة العربية. ونتيجة البحث أن البرنامج لها مزايا وعيوب وأنه يمكن الاستفادة منه بشكل كبير في حقل تعليم اللغة العربية لا سيما في الظروف التي لا تسمح الدراسة الحضورية داخل القاعات الدراسية وتضطر المدرسين لابتكارات نظم التعليم عن بعد.